EFFECTIVENESS OF A TASK-PROGRESSION LEARNING MODEL ON UNIVERSITY STUDENTS’ FOREHAND AND BACKHAND SKILLS IN TABLE TENNIS: A QUASI-EXPERIMENTAL STUDY - Rohmad; Wanuh Wiyarko (CV. TOTUS TUUS, 2026)
Low mastery of table tennis forehand and backhand strokes among university students is often linked to instruction that is insufficiently structured and does not match learners’ skill levels. Task-progression-based learning is designed to sequence practice tasks from simple to complex, enabling gradual and systematic motor-skill acquisition. This study examined the effectiveness of a task-progression learning model in improving students’ forehand and backhand stroke skills in table tennis. A quantitative quasi-experimental design was employed, involving an experimental group receiving task-progression instruction and a control group receiving conventional instruction. Skill performance was measured using standardized forehand and backhand stroke tests administered before and after the intervention. Inferential statistics (including prerequisite tests and a t-test) were used to compare skill gains between groups. Results indicated that both groups improved, but the experimental group achieved substantially higher post-test performance and improvement. The experimental group’s mean score increased from 62.45 to 82.30 (gain = 19.85), while the control group increased from 63.10 to 71.25 (gain = 8.15), with the difference in gains statistically significant. These findings suggest that progressively sequenced practice tasks facilitate more effective learning of fundamental table tennis techniques and support incremental improvement in movement quality. The study concludes that task-progression-based learning is effective and recommended for table tennis instruction in higher education. Future research should test longer interventions, examine retention and transfer to game performance, and apply task progression to other sport skills and learner profiles.